2000
DOI: 10.1161/01.cir.101.5.477
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Baseline and On-Treatment Lipid Parameters and First Acute Major Coronary Events in the Air Force/Texas Coronary Atherosclerosis Prevention Study (AFCAPS/TexCAPS)

Abstract: Persons with average TC and LDL-C levels and below-average HDL-C may obtain significant clinical benefit from primary-prevention lipid modification. On-treatment apoB, especially when combined with apoAI to form the apoB/AI ratio, may be a more accurate predictor than LDL-C of risk for first AMCE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
281
0
5

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 500 publications
(298 citation statements)
references
References 22 publications
12
281
0
5
Order By: Relevance
“…This finding is consistent with those of other large statin trials in which the relative risk reduction was similar in subjects with high, average, and low LDL cholesterol levels. [27][28][29] In the present study, there was no association between WBC and LDL cholesterol, which is consistent with studies that found no association between C-reactive protein and LDL cholesterol. 4 -6 These observations are consistent with the hypothesis that WBC and LDL cholesterol level influence cardiac risk by different pathways.…”
Section: Stewart Et Al White Blood Count Pravastatin Coronary Mortasupporting
confidence: 92%
“…This finding is consistent with those of other large statin trials in which the relative risk reduction was similar in subjects with high, average, and low LDL cholesterol levels. [27][28][29] In the present study, there was no association between WBC and LDL cholesterol, which is consistent with studies that found no association between C-reactive protein and LDL cholesterol. 4 -6 These observations are consistent with the hypothesis that WBC and LDL cholesterol level influence cardiac risk by different pathways.…”
Section: Stewart Et Al White Blood Count Pravastatin Coronary Mortasupporting
confidence: 92%
“…14,15 However, in a reproducibility study among 82 men from the Health Professionals Follow-Up Study, the intraclass correlation coefficients for plasma lipids collected 3 to 4 years apart were Ͼ0.7 for all lipids. Second, because we did not have full measurements of apoA-I, we could not assess the suggested 16,17 predictive value of apoB 100 /apoA-I. However, apoA-I did not add additional value over HDL-C in predicting CHD.…”
Section: Discussionmentioning
confidence: 97%
“…25,[27][28][29][30][31][32][33][34] Thus, the analyses presented are limited to C-reactive protein (CRP), hemoglobin A1C (hgA1C), and high-density lipoprotein (HDL) cholesterol.…”
Section: Blood Specimen Collection and Assaysmentioning
confidence: 99%